[PP.08.04] CHANGES IN RENAL ARTERY DIMENSIONS PREDICT BLOOD PRESSURE RESPONSE FOLLOWING RENAL DENERVATION. AN INTRAVASCULAR ULTRASOUND STUDY. (September 2016) - Weber, T.; Ligthart, J.; Witberg, K.; Eber, B.
Abstract : Objective: Procedural characteristics predicting blood pressure (BP) response to renal denervation (RDN) are currently lacking. The changes in renal artery (RA) dimensions induced by RDN have rarely been quantified and never been related to BP. Design and method: We prospectively investigated RAs of 17 patients (7 females, 11 diabetics, mean age 61.9 years) pre and post RDN (Symplicity Flex in 9 pts, Symplicity Spyral in 8 pts) with intravascular ultrasound (IVUS; Atlantis pro, Boston Scientific iLab). IVUS images were analyzed with QCU-CMS research software yielding global measures of RA size (RA vessel volume VV, lumen volume LV, wall volume WV), and measures of most pronounced focal changes (minimum and maximum vessel area VA, lumen area LA and wall thickness WT). Results: Pre RDN, 24 hour BP was 152/88 mmHg, mean number of ablation points was 11.8 (SD 3.8). After 1, 3, 6, and 12 months, 24 hour BP decreased by 11/6, 8/5, 16/8, and 20/9 mmHg, respectively. RDN induced a non-significant decrease in RA VV of 5.6 (SD 9.4) %, a significant decrease of RA LV of 8.9 (SD 10.4)%, and a non-significant increase of RA WV of 6.9 (SD 11.4) %. Max and min LA decreased significantly by 7.3 (SD 9.1) % and 10.5 (13.9) %, respectively, as did min VA by 6.8 (12.2) %. Max WT increased significantly by 14.1 (SD 21.1) 24 hour-based BP changes at 1, 3, 6 and 12 months were significantly and directly related to focal changes in min LA and min VA (r = 0.50–0.72, p-values 0.003–0.05). The change in min WT at 1, 3, and 12 months was significantly and inversely related to the change in systolic BP (r = −0.49, −0.54, −0.72, respectively, p = 0.006–0.05). Changes in global measures of RA size showed only moderate correlations with changes in BP. Conclusions: RDN leads to effects on global and focal RA dimensions (decrease in vessel and lumen size, increase in wall thickness). A higher degree of focal changes, particularly focal vessel narrowing and vessel thickening, may be associated with a better BP response to the procedure.